Negotiation Strategies between Pro- and Anti-Government Parliamentary Factions in Adjusting the 2017 Election Bill (Oratio Directa, 2021)
Negotiation is central to public-policy formulation when political actors hold different preferences and interests. This study examines negotiation strategies among parliamentary factions supporting and opposing the government during the adjustment of Indonesia's 2017 Election Bill. It uses a qualitative case-study approach and interprets the policy discussion through dialectical-relational and functional group-communication perspectives. The analysis focuses on the electoral system, parliamentary threshold, presidential threshold, district magnitude, and vote-conversion method. The findings indicate that negotiation proceeded through problem identification, clarification of factional interests, intensive communication, lobbying, exchange of information, comparison of alternatives, and efforts to identify shared positions. Agreement was facilitated when participants emphasized common electoral objectives and treated differences as issues to be managed through dialogue. The study concludes that policy negotiation requires structured information, active inter-faction communication, and a problem-solving orientation that preserves fairness among electoral actors.
Keywords: Negotiation strategy; Political communication; Parliamentary factions; Election Bill; Public policy